Propuesta de una estructura de costos totales para RAC LOGISTIC S.A.S que permita establecer un valor de flete competitivo en el mercado. (2024)
Efficiency and cost control are crucial for budget management, vital information for administrative decision-making in freight transportation companies. This study focuses on RAC LOGISTIC S.A.S, a company located in Bogotá, which has a fleet of 7 tractor-trailers with a capacity of 34 tons each. These vehicles transport various types of cargo to multiple destinations in Colombia.